Development of physical security protection metamodel - Ahmed Hashi, Hussein (2013)
Physical Security Management is a multidisciplinary endeavor and a very tough knowledge domain to model. It is a diffused area of knowledge that is continuously evolving and informally represented. The domain has many complex features interconnecting the physical and the social views of the world. Many international and national bodies create knowledge models to allow knowledge sharing and effective physical security management activities. These models are often narrow in focus and deal with specific organizations. Analysis of these models uncover that many physical security management activities are actually common even though organization are different. This project report creates a unified view of physical security management in the form of a metamodel that can be seen as a language for this domain. Design Research Science is a procedure of a series of thoughts and activities by which an artifact is developed and achieved. Design Science conceptualized by supports a practical research prototype that calls for the creation of innovative artifacts to solve real- world problems. The metamodel is validated and refined to serve as a representational layer to unify facilitate and further access to physical security management expertise. This aims to facilitate knowledge sharing, combining and matching different physical security management activities at different organizations. This project report synthesizes and validates a methodical metamodelling process applicable to domains represented in a diffused amid informal manner by focusing on the validation and the metamodelling process on physical security management. Comparison against other models is validation technique which is used to identify any missing concepts in the initial version of the metamodel and to also ensure its broad coverage